Prucalopride induces high‐amplitude propagating contractions in the colon of patients with chronic constipation: a randomized study. Issue 9 (7th June 2016) - Miner, P. B.; Camilleri, M.; Burton, D.; Achenbach, H.; Wan, H.; Dragone, J.; Mellgard, B.
Abstract: Background: This study compared prucalopride, a selective, prokinetic, 5‐HT4 receptor agonist, with polyethylene glycol 3350 + electrolytes (PEG3350), an osmotic laxative, on colonic motility parameters, primarily high‐amplitude propagating contractions (HAPCs) in patients with chronic constipation. Methods: This randomized, cross‐over, reader‐blinded study was conducted at a single site in the USA. The study was open to men and women aged 18–75 years who met study inclusion criteria. Colonic manometry catheters were inserted the day before investigation. On the investigation days, patients received oral 2 mg prucalopride or 2 × 13.8 g PEG3350 in solution. The primary endpoint was HAPC count (threshold: mean amplitude ≥100 mmHg, propagation ≥20 cm [HAPC1 ]) in the 12 h after treatment administration. Analyses were also conducted at two co‐primary thresholds: mean amplitude ≥75 mmHg, propagation ≥20 cm (HAPC2 ); and mean amplitude ≥75 mmHg, propagation ≥10 cm (HAPC3 ). Secondary endpoints included HAPC area under the curve (AUC), contraction force, amplitude, duration, and propagation velocity. Key Results: Thirteen women were enrolled, with 12 completing the study. Significantly more HAPC1 (8.7 ± 2.06 vs 2.9 ± 2.06; p = 0.012) and HAPC2 (9.0 ± 2.11 vs 3.3 ± 2.11; p = 0.017) were observed in the 12‐h periods with prucalopride than with PEG3350. Prucalopride significantly increased mean propagation distance and velocity (HAPC2 ) and mean AUC, force, and amplitude (HAPC3 ) compared with PEG3350. Adverse events were mild or moderate. Conclusions & Inferences: Prucalopride was superior to PEG3350 in inducing HAPCs in patients with chronic constipation. ClinicalTrials.gov number NCT01707667. Abstract : This study compared the effects on colonic motility of prucalopride vs polyethylene glycol 3350 + electrolytes (PEG3350) in patients with chronic constipation. Prucalopride was found to be superior to PEG3350 + electrolytes in improving colonic motility, as measured by the number of high‐amplitude propagating contractions, in patients with chronic constipation.